For Grades or Money? Charter School Failure in North Carolina. (August 2014) - Paino, Maria; Renzulli, Linda A.; Boylan, Rebecca L.; Bradley, Christen L.
Purpose: Charter schools are unique public schools in part because this type of school can close if it fails to meet objectives set forth by the chartering body that approved it. Thus far, however, little research has been conducted into the causes of charter school closures. In this article, we examine charter school accountability.Research Design: We consider four types of accountability to guide our event history analysis of environmental influences that affect charter school closures in North Carolina. In addition, we present two case studies of schools that closed in North Carolina to better illustrate the differing micro-level processes that can lead to the closure of a school.Findings: We find evidence that market, bureaucratic, and financial accountability processes influence the likelihood that a school will close. The initiation of closure procedures, however, is more complex than our quantitative model alone suggests and our two case studies illustrate the key role that financial accountability plays in charter school closures in North Carolina.